Feto-maternal haemorrhage: a review after and a case report - Bhandari, Ruchi; Khemani, Manju; Mustafa, Asif (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Feto-maternal haemorrhage is the transmission of fetal blood cells to the maternal blood stream. It is quite common in small volumes- occurring in most pregnancies. Large volumes of feto-maternal haemorrhage can have serious consequences. Some risk factors are identified, but they are not always present. Decreased perception of fetal movements is most important clinical sign, together with a pathological NST. Prompt diagnosis and immediate obstetric care is fundamental, as serious risk to the fetus might result from this condition. Author described the case report of 35 years old G3P1L1A1 with 37 weeks 5 days pregnancy, who came in outpatient department with reduced perception of fetal movements during the previous 10 hours. There was no history of abdominal trauma. Cardiotocograph showed nonreactive NST with minimal beat to beat variability for more than 40minutes. An emergency caesarean section was performed and a female limp baby delivered with heart rate <60/minutes, pale, no respiration and no reflexes. Baby resuscitated with bag and tube ventilated. APGAR score was 3/5/6 at 0, 1, and 5 minutes. Fetal haemoglobin at the first hour of life was 3.0gm/dl. Kleihauer-Betke test revealed 265.7ml of fetal erythrocytes in the maternal blood stream. Despite being rare, it is important to detect a massive feto-maternal haemorrhage. Fetal anemia could be suspected, but the diagnosis was only made after delivery. This case reveals the importance of keeping a high suspicion in obstetric practice, as feto-maternal haemorrhage is a rare but potentially catastrophic event for a fetus.